Nanocomposite biosensor tracks honokiol-induced oxidative stress dynamics in 3D hydrogel-cultured lung cancer cells - Yuxuan Zhu; Zhichao Huang; Shichao Tian; Qi Wang; Fan Wu; Jingwen Liu; Ping Wang; Hao Wan; Liujing Zhuang; Deming Jiang (Microsystems & Nanoengineering)
Abstract In cancer cells, higher reactive oxygen species (ROS) than normal cells were observed due to hypermetabolism. The redox balance in cancer cells relies on accordingly upregulated antioxidant capacity. By manipulating oxidation and antioxidant systems, chemotherapeutic drugs can selectively kill cancer cells without hurting normal cells. As three-dimensional (3D) in vitro models, such as spheroids and organoids, have become widely used in cancer research, traditional detection methods (e.g., absorption tests or titration) are inadequate for detecting in 3D environments. Thus, it is crucial to find a new method to detect oxidative stress of 3D in vitro cancer models. Here, a nanocomposite electrochemical biosensor was exploited to evaluate oxidative stress of cancer cells cultured in the 3D environment. The oxidation-regulatory capacity of honokiol, a Magnolia genus-derived anti-cancer molecule, was evaluated. A screen-printed electrode (SPCE) was modified with reduced graphene oxide (RGO) and platinum nanoparticles (Pt NPs) to get Pt NPs/RGO/SPCE. Then the gelatin methacrylate/reduced graphene oxide (GelMA/RGO) hydrogel was applied to immobilized NCI-H1975 in a 3D bionic environment to get NCI-H1975/GelMA/RGO/Pt NPs/RGO/SPCE. After optimizing the experiment condition, the Pt NPs/RGO/SPCE showed a detection threshold of 0.65 μM and a linear field from 1 to 10 μM for H2O2 detection while the NCI-H1975/GelMA/RGO/Pt NPs/RGO/SPCE sensitively responded to H2O2-induced oxidative stress. By utilizing the NCI-H1975/GelMA/RGO/Pt NPs/RGO/SPCE we found honokiol (a natural polyphenol constituent) inhibits NCI-H1975 by inducing oxidative stress. This simple cell-based electrochemical biosensor can in situ evaluate oxidative stress of 3D cancer models conveniently. It can also be easily extended to the study of the mechanism of action of other drugs and holds broad application prospects in the fields of new drug development and drug repurposing.